Inhibitory Effect of Polydatin Against Aeromonas hydrophila Infections by Reducing Aerolysin Production - Dong, Jing; Yan, Tianhui; Yang, Qiuhong; Zhou, Shun; Song, Yi; Liu, Yongtao; Ma, Liang; Xu, Ning; Yang, Yibin; Ai, Xiaohui (Frontiers in Veterinary Science, 2022)
The fast-growing demand for aquatic products has led to the rapid development of aquaculture. However, diseases caused by bacterial pathogens result in severe economic losses all over the world. Although the introduction of antibiotics to aquaculture decreased the mortality of infectious diseases, the emergence of antibiotic resistance caused treatment failure. Therefore, drugs with novel strategies are needed for combatting infections caused by resistant bacterial strains. In the present study, aerolysin was identified as a target for developing drugs from natural compounds against Aeromonas hydrophila (A. hydrophila) infections. We found that polydatin without an inhibitory effect against A. hydrophila growth could decrease the hemolysis mediated by aerolysin. In both western blot and qPCR assays, the addition of polydatin decreased the production of aerolysin by downregulating the aerolysin encoding gene. Moreover, cell viability and animal studies found that polydatin could reduce the pathogenesis of A. hydrophila both in vitro and in vivo. Taken together, these findings provided a novel approach and candidate for treating resistant A. hydrophila infections in aquaculture.